Educational and schooling thought in Piramerd's Poetic Proverbs (Raparin Journal of Humanities (RJH), 2024)
Proverbs are product of each society's thoughts and views on phenomena and events and their worldview for the future, which have appeared as a result of the experiences of enlightened people and the whole of society has participated in expressing and formulating them. Among them, the poetic proverbs which are the work of experienced and wise persons that generated them, and afterwards became the property of society which have an important value for any subject and purpose, that we want to know the people's opinion about. In the view of importance of poetic proverbs and their impact on education, this study investigates Piramerd's Poetic Proverbs entitled (Educational and schooling thought in Piramerd's Poetic Proverbs). Piramerd looks for importance of education in the view of Kurdish society in that era and importance of education in Kurdish proverb in particular, what was the status of education at that time? What was the desired trend of education? The study consists of two sections: the first section includes the concept of proverb, poetic proverb, and the importance of education and the role of educational proverbs. In the second section, on the basis of warning, avoidance, instructions, guidelines, objectives of the poetic proverbs and their contents are explained and shedding light on their aims; thereafter, the perspectives and worldviews are identified. Finally, the results are showed.